(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: Sexual relationships change due to the physical and psychological changes occurring during pregnancy. Physical, emotional and economic anxieties in pregnancy often affect the couple’s marital relationship and their sexual responses to each other and can thus adversely affect their overall relationship and the family’s mental health. The present comparative study was conducted to examine the relationship between the wealth index and pregnancy-related anxiety in each trimester of pregnancy and their effect on sexual dysfunction. Methods: This cross-sectional study was conducted on 450 pregnant Iranian women in 2016. Data were collected using the Female Sexual Function Index (FSFI), the Pregnancy-Related Anxiety Questionnaire, the Wealth Index and a demographic questionnaire. Data were analyzed in SPSS-23. Results: As gestational age increased, sexual dysfunction increased too. The highest degree of sexual dysfunction was reported in the first and third trimesters. Sexual arousal disorders were reported in all the trimesters and dyspareunia was reported in the second trimester. The greatest pregnancy concerns were reported in the third trimester. As the age of the subjects and their spouse increased, the prevalence of sexual dysfunction also increased and the level of pregnancy-related concerns decreased. A higher wealth index was associated with a reduced pregnancy-related anxiety. Sexual dysfunction was less observed in those with higher levels of education (P<0.05). Discussion and Conclusion: The wealth index can affect sexual performance through the mediating effects of pregnancy-related anxiety. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.401-408